ASSESSMENT OF YIELD COMPONENTS AND THEIR ASSOCIATION IN F2 POPULATIONS OF WHEAT - Iqbal, Touheed; Saad Saeed, Ghulam Hassan, Iqbal Hussain (Journal of Scientific Agriculture, 2017)
Keeping in view the role of wheat in Pakistan, the current research was conducted to compute the extent of transmissibility and to derive information on the correlation of grain yield with its component traits. Sixteen F2 populations of wheat and their eight parental lines were evaluated at the University of Agriculture, Peshawar-Pakistan during wheat season of 2013-14. Experiment was conducted in randomized complete block design with three replicates. Analysis of variance manifested significant differences among genotypes for all the studied traits. Similarly, mean squares due to parents, F2 populations and parents vs. F2`s were also significant for all the traits under study except harvest index. On the basis of mean performance, maximum grain yield plant-1 among parents was given by Fakhr-e-Sarhad (27.16 g) and PS-05 (26.06 g), while among F2 populations, maximum grain yield plant-1 was given by cross combinations Barsat / Siren (27.93 g), AUP-5008 / Siren (26.09 g) and Tatara / PS-05 (25.65 g). The assessments of heritability and genetic advance manifested that F2 populations, Saleem-2K / Janbaz, Tatara / F.S, AUP-5008 / PS-05 and Tatara / PS-05 had highly heritable characters along with high genetic advance, which offer an opportunity for earlier selection. Hence, more emphasis should be given to these crosses in future wheat breeding programs. Moreover, the perusal of correlation analysis revealed that traits like days to maturity, flag leaf area, plant height, fertile tillers plant-1, biological yield and harvest index appeared to be most essential sources of affecting the final yield, suggesting that upsurge in wheat yield could be admissible by selecting these traits.